Leadership Analysis in Achieving Patient Satisfaction At the Mabelopura Health Center Service, Palu City, Central Sulawesi Province - Sri Naharindah Ningsih S; Oscar Jayanegara (Dinasti International Journal of Education Management And Social Science, 2025)
The concept of leadership reliability in a health center is the first priority and is preventive in providing individual health facilities. Patient satisfaction in health centers is greatly influenced by the leadership method in fulfilling various variables to the maximum. This study aims to determine the significance of the level of patient satisfaction with the leadership method in the service management of the Mabelopura Health Center in Palu City, Central Sulawesi Province in relation to the fulfillment of the variables of facilities and infrastructure (tangible), concern (empathy), reliability (reliability), responsiveness (responsive), certainty (assurance). Data collection through a questionnaire in the form of empirical reliability questions to 80 respondents which were then processed and analyzed through SPSS statistical tests in the form of normality tests, multicollinearity tests, multiple linear regression tests, namely the T test and F test. The truth of the hypothesis shows that there is a real influence both partially and simultaneously on the leadership method in fulfilling the variables of tangible, empathy, reliability, responsiveness, assurance on patient satisfaction values,, so that Ho is rejected and H1 is accepted. It was found that there was no multicollinearity because the tolerance value was > 0.1 (alpha 10%) and VIF < 10. The results of T count > T table and the results of the F test obtained a sig value of 0.000 < 0.05.